ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PERPINDAHAN MEREK DENGAN REFERENCE GROUP SEBAGAI VARIABEL MODERATING (Studi kasus pada pengguna provider Indosat M3 di Kota Semarang) - Ariani, Yulia Putri (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2014)
Samples of this study are the ones who are still using Indosat IM3 and use other providers inthe area of Semarang with the number of respondents is 150 people. Techniques analyzedusing Structural Equation Modeling (SEM) with WarpPLS program version 2.0. The data hasbeen tested using validity to test the validity of the list of questions by looking at the value ofAPC, ARS, VIF, AVIF and discriminant validity whereas reliability test using the approach ofcomposite reability and Cronbach’s Alpha and hypothesis testing is measured based on asignificance level of 5% .Data results show that the model proposed in this study can be accepted, so it can be concludedthat the higher variety seeking behavior, the higher the interest in brand switching (hypothesis1) with a path coefficient of 0.125, the higher the effectiveness of the lower interest advertisingbrand switching (hypothesis 2) with a path coefficient of -0.118, the higher the customer satisfaction,the lower the interest in brand switching (hypothesis 3) with a path coefficient of -0694, thehigher the customer satisfaction, the lower the interest in brand switching, if the dominantreference group (hypothesis 4) with path coefficient of -0.151.